Research on Microstructure, Mechanical Properties and Electromagnetic Shielding Properties of Mg-6Zn-3Sn-0.5Cu Alloy - Liu, Yan Hui; Ma, Ming Long; Li, Xing Gang; Li, Yong Jun; Shi, Guo Liang; Yuan, Jia Wei; Zhang, Kui (Frontiers in Materials, 2021)
In this paper, the microstructure, electromagnetic shielding properties and mechanical properties of Mg-6Zn-3Sn-0.5Cu alloys are studied. As indicated from the results, the phases in the as-cast alloy comprise α-Mg, MgZnCu, Mg2Sn and Mg2Zn3 phases. After homogenization, Mg2Sn and Mg2Zn3 phases are decomposed, but MgZnCu phase remains. Complete dynamic recrystallization (DRX) occurs in the extrusion process, and the spherical Mg2Sn phase precipitates dynamically. Due to considerable rod-like β′1 phases precipitate by complying with the [0001] Mg direction, the mechanical properties of aged alloys are remarkably enhanced. The peak-aged alloy achieves the tensile strength of 366 MPa, the yield strength of 358 MPa and the elongation of 7%. With the increase in the size of the β′1 phase, the mechanical properties of the over-aged alloy are reduced. Since the phases precipitate, the electrical conductivity of the alloy is enhanced, and the internal reflective interface increases, so the aged alloys exhibit improved electromagnetic shielding performance. The electromagnetic shielding efficiency of the peak-aged alloy exceeds 105 dB in the range of 30-1500 MHz, showing the best match between mechanical and electromagnetic shielding properties.